2019
DOI: 10.1245/s10434-019-07957-w
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Laparoscopy as a Selection Tool for Patients with Colorectal Peritoneal Metastases to Prevent a Non-therapeutic Laparotomy During Cytoreductive Surgery

Abstract: Objective. The aim of this study was to evaluate the introduction of diagnostic laparoscopy (DLS) in patients with colorectal peritoneal metastases (PM) to prevent nontherapeutic laparotomies during cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS ? HIPEC). Methods. Patients with histologically proven colorectal PM who underwent a laparotomy for potential CRS ? HIPEC from January 2006 to January 2019 were retrospectively identified from a prospectively maintained database. In 2012, DLS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…In this study, the median survival of patients who had CRS/HIPEC was 36.4 months. 1 This prolonged survival is similar to the 41-month median survival of patients in the PRODIGE 7 trial reported at ASCO. 8 In both studies, patients are treated with a combination of systemic chemotherapy and CRS/HIPEC.…”
supporting
confidence: 75%
See 3 more Smart Citations
“…In this study, the median survival of patients who had CRS/HIPEC was 36.4 months. 1 This prolonged survival is similar to the 41-month median survival of patients in the PRODIGE 7 trial reported at ASCO. 8 In both studies, patients are treated with a combination of systemic chemotherapy and CRS/HIPEC.…”
supporting
confidence: 75%
“…Concerns regarding the safety of DLS in this patient population, given the high rate of prior surgery and the potential risk of port-site metastases, have not been confirmed. Hentzen et al 1 as well as prior reports, 2,3,7 find no significant complications; therefore, avoiding the alternative of a non-therapeutic laparotomy is well worth the risk of a DLS.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Current radiological imaging techniques are valuable in the detection of distant metastasis but underestimate the extend of peritoneal disease 9–11. To prevent unnecessary open-close procedures/laparotomies in patients with a PCI >20, a diagnostic laparoscopy (DLS) is recommended during preoperative work-up for CRS-HIPEC 12 13. DLS can prevent up to 40% of open-close procedures 13.…”
Section: Introductionmentioning
confidence: 99%